(3GdYbjOI GdeajOI YbjOI GdSda hCUMGH GdMOjKs - (3CHh YKeGf ESeGYjd Hf YHO GdQMef GdUCHhfjs ((3YHO GdYRjR Hf YHO Gddg Hf eMeO Hf SdjeGf Hf YGeQ s)
(3ChdgG (B:s
(3CNHQfG bGVi GdbVGI HOeTb fXGe GdOjf YeQ Hf GHQGgje Hf eMeO Hf eadM GdUGdMi GdMfHdi ELGRI eTGagI CeG HYO aEfi deG hQOJ BeO WHQSJGf hHdGO LjdGf eJhLgkG Edi HjJ Gddg GdMQGe hRjGQI bHQfHjg eMeO Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3GdPjf jSJeYhf Gdbhd ajJHYhf CMSfg hjJeSchf ai OfjGge eOI eMjGge HGdcJGH hGdSfI hLfHfG GdCghGA GdeVdI hGdBQGA GdeVeMdI hGdCShGA GdePdI aVdkG efg hefg Bejf BNQg hGdMeO ddg hMOg hUdi Gddg hSde Ydi SjOfG eMeO hYdi Bdg hUMHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG JQLeI ddeUfas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds